2019
DOI: 10.1111/hae.13734
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based surveillance of haemophilia and patient outcomes in Indiana using multiple data sources

Abstract: IntroductionEpidemiological surveillance of haemophilia through linkage of medical records within a US state has not been conducted in 20 years.AimThe Indiana Haemophilia Surveillance Project aims to identify all persons with haemophilia who resided in Indiana in 2011‐2013 and to determine the percentage of patients in Indiana cared for at a federally recognized haemophilia treatment centre (HTC).MethodsA retrospective review of medical charts was conducted to identify haemophilia cases during the surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…This finding was unexpected since the HSS provided more complete ascertainment in the states studied, and it is known that not all people with haemophilia in the United States receive care in these HTCs. While the exact proportion is unknown, estimates from a more recent study that used the same methodology as the HSS suggest that closer to 80% of the haemophilia population receive care in this HTC network versus the 67% measured in the HSS 1,2 . Based on the 21 748 patients we report in this study and our assumptions about the proportion of US haemophilia males who receive care in HTCs (between 67% and 80%), we estimate that a total of between 29 761 and 32 985 males with haemophilia live in the United States today.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding was unexpected since the HSS provided more complete ascertainment in the states studied, and it is known that not all people with haemophilia in the United States receive care in these HTCs. While the exact proportion is unknown, estimates from a more recent study that used the same methodology as the HSS suggest that closer to 80% of the haemophilia population receive care in this HTC network versus the 67% measured in the HSS 1,2 . Based on the 21 748 patients we report in this study and our assumptions about the proportion of US haemophilia males who receive care in HTCs (between 67% and 80%), we estimate that a total of between 29 761 and 32 985 males with haemophilia live in the United States today.…”
Section: Discussionmentioning
confidence: 83%
“…At the time of the HSS, 67% of the identified population with haemophilia in the six‐state surveillance catchment area received some care in an HTC during a three‐year period 1 . A more recent population‐based study conducted in Indiana found that 81.7% of males with haemophilia identified in that state had visited an HTC during the period 2011‐2013 2 …”
Section: Introductionmentioning
confidence: 99%
“…45 In another CDC-sponsored study, HTCs were shown to reduce mortality among persons with hemophilia by 40% as well as decrease healthcare resource utilization. 45 , 46 Comprehensive care is one of the essential principles in the model for the development of a national healthcare program for patients with hemophilia. 31 HTCs have been established to guarantee patients and families access to all services essential for the management of their bleeding disorder.…”
Section: The Evolution Of Comprehensive Care For Hemophiliamentioning
confidence: 99%
“…45 More recently, in one US HTC, approximately 81.7% of persons with hemophilia receive care at least once a year. 46 Those that benefit from care at HTCs have a reduced rate of emergency department (ED) utilization and an increased rate of prophylaxis and self-infusion compared to those receiving care outside of the HTC network. 46 …”
Section: The Evolution Of Comprehensive Care For Hemophiliamentioning
confidence: 99%
“…Table 7 shows that the average number of PWHA enrolled in the HTCs is estimated at 8 per 100,000 males with 54% being severe 6 whereas a recent US study reports 12.7 per 100,000 males (34% severe). 21…”
Section: Re Sultsmentioning
confidence: 99%